The Dynamics of Viscoelastic Layered Systems Studied by Surface Acoustic Wave (SAW) Sensors Operated in a Liquid Phase. (2017) - Vikström, A.; Voinova, M.V.
Abstract: We theoretically study a three-layer continuum model of a surface acoustic wave sensor where the two overlayers are allowed to be viscoelastic. This case is particularly important in biosensing, where soft materials submerged in fluids are commonplace. From the general dispersion equation, we calculate the phase velocity shift and the wave attenuation. We show that there is a viscoelastic coupling between the overlayers which results in unintuitive behavior, e.g., the addition of viscous loading to a soft-film sensor can reduce the attenuation.